From Theology And Philosophy To Psychology In The West - Rachel Riddell (Theological Journal Kerugma, 2022)
This study aims to explore the Western epistemological shift over the last five hundred years: a move from Christianity to secularism. To do this, we will address key philosophical, theological and psychological developments and their respective proponents in history. We will also note the consequences of these ideas on broader human society. We will approach this topic from a Biblical epistemological foundation, allowing our faith in God to guide our interpretation of these developments. This article is divided into five key sections, each addressing the concerns of different ages in history. We discover that relativism is what binds all of these ages and developments together.